Towards Industrial Revolution 4.0: Employers' Expectations on Fresh Engineering Graduates - Azmi, Aini Najwa; Kamin, Yusri; Noordin, Muhammad Khair; Nasir, Ahmad Nabil Md. (International Journal of Engineering and Technology, 2018)
From the pass until now, the industry was affected by technological change and innovation. These paradigms are called industrial revolutions. These revolutions were caused by mechanization (1st industrial revolution), use of electrical energy (2nd industrial revolution) and electronics and automation (3rd industrial revolution). All these industrial revolutions did influence only the production itself, but also the labour market and the educational system as well. Currently, due to the development of digitalization and robotics, we are facing the next industrial revolution, known as the Industry Revolution 4.0. The emerging technologies have huge effect on the education of people. Only qualified and highly educated employees will be able to control these technologies. The skills needed by employers' in the Industry 4.0 have change due to the changes of the technologies. In this paper, we present the non-technical skills those are demanded by employers' in Industry 4.0 based on recent studies by doing meta-analysis technique. In addition, interviews with five employers have been done to clarify the meta-analysis results. Based on the results, the non-technical skills which are demanded by employers are communication skills especially in English, teamwork skills, critical thinking and problem-solving skills, entrepreneur skills and computer skills. Universities should be exposed their students with much more of interdisciplinary teaching, research, innovation and valuable industrial training to meet current demands of industries.